Review: Traditional knowledge of the Dayak Tribes (Borneo) in the use of medicinal plants - FATIHA RISTYA AZ-ZAHRA; NERIZA LARAS WIDYA SARI; RAIHANI SAPUTRY; GILANG DWI NUGROHO; TEGUH PRIBADI; SUNARTO SUNARTO; AHMAD DWI SETYAWAN (Society for Indonesian Biodiversity, 2021)
Abstract. Az-Zahra FR, Sari NLW, Saputry R, Nugroho GD, Sunarto, Pribadi T, Setyawan AD. 2021. Review: Traditional knowledge of the Dayak Tribe (Borneo) in the use of medicinal plants. Biodiversitas 22: 4633-4647. Dayak is the name for the native inhabitants of the island of Borneo. The Dayak Tribe uses natural and forest products in plants as traditional medicine for health treatment. This study aims to obtain information about the utilization of medicinal plants in the Dayak Tribe. The knowledge about traditional medicine by utilizing medicinal plants has been obtained from their ancestors since ancient times and inherited from generation to generation. The use of various medicinal plants used by the Dayak Tribe has differences in terms of the part of the plant taken, how to process it, and how to use it. This is because each Dayak Sub-tribe has its role model for using these medicinal plants. For example, the leaves are used in one area, and it could be that the plant roots are used in other areas. This paper reviews the use of medicinal plants to treat various diseases by 6 Dayak sub-tribes, namely: Desa Dayak Sub-tribe (member of Iban Dayak), Jangkang Dayak Sub-tribe (member of Klemantan Dayak), Bakumpai Dayak Sub-tribe (member of OtDanum-Ngaju Dayak), Kenyah Dayak Sub-tribe (member of Apokayan Dayak), Tagol Dayak Sub-tribe (member of Murut Dayak), and Siang Dayak Sub-tribe (member of Punan Dayak). The results from 6 Dayak Sub-tribes revealed 63 families of plants from which 133 species. The family most widely used for medicinal plants, namely Euphorbiaceae, consists of 9 species, and the leaf is the most commonly used part of the plants (47%). The traditional knowledge of the Dayak Tribe in utilizing plant resources will significantly help preserve biodiversity and domestication of medicinal plants. Suppose medicinal plants are exploited more than they should. In that case, it will undoubtedly have a significant impact on their availability in the forest area, and if it continues, it will cause the extinction of certain species. This implies the importance of preserving local wisdom in the Dayak Tribe so that the use of nature is done wisely and so that it remains sustainable. By knowing the benefits of medicinal plants, Dayak Tribe will want to conserve these medicinal plants to be used in the future.